Rural and Urban Differences in the Eye Health of High School Students - Kusnawan, Andi; Musa, Ine Renata; Setiadinata, Jimmy (Althea Medical Journal, 2015)
Background: Visual impairment is a serious health problem. The World Health Organization (WHO) estimates that 80% of the incidence of visual impairment occurring globally could be prevented or treated. Several factors responsible for high rates of uncorrected refractive errors are the lack of awareness about the early detection on the unequal distribution regarding health services and a culture of compliance. This study was aimed to identify the differences of the level of visual acuity and self-perception of the visual functions between high school students in the urban and rural areas.Methods: A cross sectional study was conducted among 94 high school students in two different schools, urban and rural areas during November 2012, using the simple random sampling technique. The study was performed through interviews and examination of visual acuity using Rapid Assessments of Avoidable Blindness. The collected data were analyzed using Mann-Whitney test.Results: A total of 93.6% of respondents had good visual acuity. Self-perception of the visual functioning test showed that most respondents gave good answer. The statistical test using Mann-Whitney showed that there was no difference in level of visual acuity and self-perception of visual function between urban and rural students (p>0.05).Conclusions: Most of the high school students have good visual acuity and good self-perception of their visual function but there is no difference between rural and urban areas.Â DOI:Â 10.15850/amj.v2n3.507